Decentralised control and fault ride‐through of a multi‐microgrid system. Issue 3 (12th July 2019) - Sahoo, Saroja Kanti; Kishore, Nudurupati Krishna; Sinha, Avinash Kumar
Abstract : A multi‐microgrid (MMG) system comprises of a cluster of microgrids interconnected for reliable and efficient operation in grid connected as well as islanded modes. In this study, the fault‐ride‐through capability of an MMG system is addressed. A solution to under‐voltage and over‐current scenarios arising due to severe short‐circuit faults in inverter‐interfaced MMG system is proposed for grid‐connected and islanded modes. The MMG system has the primary sources as the solar photovoltaic system, static synchronous compensator, and wind energy‐based generation units with an additional battery as the backup source at the dc link of individual microgrids. Gate turn‐off thyristors based fault‐current limiters are considered at the individual microgrid level of the MMG system. A sliding‐mode control is employed in the decentralised controllers of the interfacing voltage‐source converters and bidirectional buck–boost converters for output current control. Accurate voltage, current, and frequency control are achieved during the fault by incorporating the proposed control strategies. The proposed decentralised control in the MMG system is experimentally verified in real time using a real‐time digital simulator (OP4510) from OPAL‐RT.